Acute graft-versus-host disease, invasive aspergillosis and Clostridium difficile colitis after peripheral blood stem cell transplantation: A complex network of causalities and a challenge for prevention. (June 2015) - Khanafer, Nagham; Neuraz, Antoine; Bénet, Thomas; Cour, Martin; Persat, Florence; Labussière, Hélène; Argaud, Laurent; Michallet, Mauricette; Vanhems, Philippe
Abstract: Graft-versus-host disease (GVHD) is a known risk factor for invasive aspergillosis (IA), but remains poorly studied in relation to Clostridium difficile infection (CDI). We report a case of a 58-years-old patient who developed an IA within a protected room, CDI and GVHD after allogeneic allogeneic peripheral blood stem cell transplantation (PBSCT). Factors associated with this complex condition in patients receiving allogeneic PBSCT need to be identified. Highlights: We describe a complex life-threatening condition after allogeneic PBSCT. GVHD may increase the risk of CDI and CDI may increase the risk of GVHD. Importance of surface monitoring in hematopoietic units. Need to identify factors associated with GVHD, CDI and IA after allogeneic PBSCT.